Membangun Brand Loyalty Mobil Listrik di Batam Melalui Strategi Pemasaran: Sebuah Studi Analisis - Sia, Zendi; Qadri, Rizni Aulia; Purwianti, Lily (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In this modern era, the level of public awareness regarding the use of environmentally friendly products tends to increase. This can be seen from the increase in the number of electric car users in various cities in Indonesia, including Batam City. The purpose of this research is none other than to analyze the effect of environmental beliefs and environmental knowledge on the formation of brand loyalty through the mediating role of environmental concern and environmentally friendly brand image. The research methodology used is quantitative, with a causality design (cause and effect between research variables), and data analysis is carried out using SMARTPLS software. The research results reveal that environmental beliefs and environmental knowledge both have a significant influence on environmental concern. Concern for the environment has a significant influence in shaping an environmentally friendly brand image. Furthermore, green brand image is the main factor driving increased brand loyalty. Environmental concern and environmentally friendly brand image able to act as mediators in connecting the influence of environmental beliefs and environmental knowledge with brand loyalty for electric car products in Batam City.